Prediction of school outcome after preterm birth: a cohort study - Odd, David (Arch Dis Child, 2019)
OBJECTIVE: To identify if the educational trajectories of preterm infants differ from those of their term peers. DESIGN: This work is based on the Avon Longitudinal Study of Parents and Children (ALSPAC). Educational measures were categorised into 10 deciles to allow comparison of measures across time periods. Gestational age was categorised as preterm (23–36 weeks) or term (37–42 weeks). Multilevel mixed-effects linear regression models were derived to examine the trajectories of decile scores across the study period. Gestational group was added as an interaction term to assess if the trajectory between educational measures varied between preterm and term infants. Adjustment for possible confounders was performed. SUBJECTS: The final dataset contained information on 12 586 infants born alive at between 23 weeks and 42 weeks of gestation. MAIN OUTCOME MEASURES: UK mandatory educational assessments (SATs) scores throughout educational journal (including final GCSE results at 16 years of age). RESULTS: Preterm infants had on average lower Key Stage (KS) scores than term children (−0.46 (−0.84 to −0.07)). However, on average, they gained on their term peers in each progressive measure (0.10 (0.01 to 0.19)), suggesting ‘catch up’ during the first few years at school. Preterm infants appeared to exhibit the increase in decile scores mostly between KS1 and KS2 (p=0.005) and little between KS2 and KS3 (p=0.182) or KS3 and KS4 (p=0.149). CONCLUSIONS: This work further emphasises the importance of early schooling and environment in these infants and suggests that support, long after the premature birth, may have additional benefits.